Role of Integrated Nutrient Management for Sustainable Maize Production - Almaz Meseret Gezahegn (International Journal of Agronomy)
Boosting crop productivity can be attained through the application of inorganic fertilizer; however, safeguarding the environment for future generations is overbearing especially for continuous increase in the world population. Sustainable crop productivity might be attained through the judicious use of both organic and inorganic fertilizers. The substitution of parts of inorganic fertilizers with organic fertilizer could maintain and sustain soil productivity and improve crop productivity. This paper has reviewed the past research work carried out by various scientists. A comprehensive literature review revealed that integrated nutrient management enhances maize yield, nutrient uptake, and economic return compared with the sole application of organic and inorganic fertilizers.